Sustainability analysis of tomato jellyfish (Crambione mastigophora) fisheries resources management in Saleh Bay Waters, Sumbawa Island, Indonesia - EVRON ASRIAL; MUHAMMAD MARZUKI; HAMID; ruly isfatul khasanah (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Asrial E, Marzuki M, Hamid, Khasanah RI. 2021. Sustainability analysis of tomato jellyfish (Crambione mastigophora) fisheries resources management in Saleh Bay Waters, Sumbawa Island, Indonesia. Biodiversitas 22: 512-520. The tomato jellyfish (Crambione mastigophora) or gullung (local term), is endemic in Saleh Bay, Sumbawa Island, Indonesia and has been utilized as an additional livelihood by fishermen for last two decades. Its commonly caught by 2-4 fishermen/boat using scoop net, wooden fishing vessels, and lamps as attractors and collectors of jellyfish. This study aims to determine the sustainability of jellyfish fisheries management. A survey-dependent method with sampling, observation, dialogue, and documentation techniques was applied for data compilation. The rapid appraisal for jellyfish fisheries - six dimensions (Rapjellyfish-6D), based on Rapfish technique, is utilized for analysis of the sustainability status of jellyfish fisheries management. This paper describes the sustainability analysis results for two of the six dimensions of jellyfish fisheries management, namely the technological dimension (13 attributes) as an input factor and the economic dimension as an output factor (14 attributes). At present, around 8-30 baskets/boat/day of jellyfish mouth-arms are being sold to the buyers in Saleh Bay. This catch's profit is divided between the fishermen (3 parts) and the boat owner (2 parts). The analytical results show the revenue per cost ratio (R/C Ratio) as 4.75 which means that every 1.00 Indonesian Rupiah (IDR) the cost of catching jellyfish will generate IDR 4.75. The breakeven point (BEP)Price is IDR 13,158 and BEPProduction is 3.13 and 8.33 baskets/trip for the assumed price of IDR 80,000 and IDR 30,000. The technological (36.13%) sustainability status and economic (49.64%) dimension is Less Sustainable. The leverage analysis results indicate that the group of sensitive attributes in the technological and economic dimensions, respectively, consists of 5 attributes and 3 attributes. All sensitive attributes have an impact on the low value of management sustainability. The sustainability of jellyfish fisheries management in Saleh Bay has been supported by a choice of environmentally friendly fishing methods. Besides, the mouth-arm price is formed from an oligopsony market system that is not profitable for fishermen. It is suggested to the village government to build an integrated and environmentally friendly scyphozoan facility to neutralize the liquid waste generated from scyphozoan processing.